PENERAPAN SUPERVISI KLINIS UNTUK PERBAIKAN KEGIATAN BELAJAR MENGAJAR DI MADRASAH ALIYAH PARADIGMA PALEMBANG - Muhammad Guntur Damsik (Conciencia, 2017)
One of the main tasks and supervisory section is to provide guidance to teachers, both religious teachers in public schools or teachers at the madrasa through supervision. But this Tupoksi based on observation data seems still weak. To know objectively about the above, this research was carried out. The problem problems that were deliberately raised in this study were: How were the teaching and learning activities in the Palembang Paradigm of Madrasah Aliyah? What is the implementation of clinical supervision at the Palembang Paradigm Madrasah Aliyah? Is there a relationship between the implementation of clinical supervision and teaching and learning activities in the Palembang Paradigm of Madrasah Aliyah? Regarding the formulation of the problem above, the purpose of this study is: To find out about teaching and learning activities in the Palembang Islamic Paradigm. To find out the implementation of clinical supervision at the Palembang Paradigm of Madrasah Aliyah. To find out the relationship between the implementation of clinical supervision and teaching and learning activities at the Palembang Islamic Senior High School Paradigm. The research method used in this study is descriptive quality by using 5 teachers as key informants and 18 teachers as respondents. Because in addition to interviews, this study used a quiz to strengthen data that had been obtained from interviews. After the data is collected, it is then processed qualitatively. There are three stages carried out in this data analysis (1) data reducation, meaning that the author summarizes the main points of the data, (2) display data, meaning to sort data based on cards or charts and (3) conclusión drawing or verification , meaning to conclude and provide estimates or interpret data collected. Thus the next data processing and recording will be carried out by improving documentation and matching it with accurate data. Based on the data analysis, the results of the study can be stated, namely: 1. Teaching and learning activities of teachers in the MA Paradigm of Palembang before clinical supervision is classified as poorly. Of the seven aspects assessed, an average value of 3 or 20% is obtained for the classification already implemented according to the indicators. Then 4.43 or 29.53% for the moderate classification and 7.57 or 34.76% for the classification did not carry out teaching according to the indicator. 2. Implementation of clinical supervision at Madrassah Aliyah (MA) The paradigm has been going well even though it has not been maximized. Of the 30 technical supervision items that needed to be implemented only 10 items (33.3%) were implemented. 3. There is a relationship between the implementation of clinical supervision and teaching and learning activities of teachers at the MA Paradigm. From the observations it is known that the teaching and learning activities of teachers at the MA Palembang Paradigm after academic supervision are classified as good or in accordance with what is expected even though it is not optimal because there are still teachers whose teaching methods are not good. Of the seven aspects assessed, the average score of 9 or 59% is obtained for the classification that has been implemented according to the indicators. Then 4 or 27% for the moderate classification and 2 or 14% for the classification did not carry out teaching according to the indicator.